Characteristics and Moral Values From “Encanto” Disney as a Enhancing Strategy in Character Building - Evi Novalin Bako; Reza Fahlevi (English Language Teaching Prima Journal (ELT), 2022)
This research focuses on key truths about a family matter that adolescents may start to absorb at specific educational age hence teachers can teach this using the literature film Encanto by Disney. We discovered 10 fundamental moral ideals in the film, as well as 7 individuals from whom we might learn. The data gathering approach being used is qualitative . The focus of this research is the film